Immediate versus delayed removal of urinary catheter after laparoscopic hysterectomy: a randomised controlled trial. (1st March 2019) - Sandberg, EM; Twijnstra, ARH; van Meir, CA; Kok, HS; van Geloven, N; Gludovacz, K; Kolkman, W; Nagel, HTC; Haans, LCF; Kapiteijn, K; Jansen, FW
Abstract : Objective: To evaluate if immediate catheter removal (ICR) after laparoscopic hysterectomy is associated with similar retention outcomes compared with delayed removal (DCR). Study design: Non‐inferiority randomised controlled trial. Population: Women undergoing laparoscopic hysterectomy in six hospitals in the Netherlands. Methods: Women were randomised to ICR or DCR (between 18 and 24 hours after surgery). Primary outcome: The inability to void within 6 hours after catheter removal. Results: One hundred and fifty‐five women were randomised to ICR ( n  = 74) and DCR ( n  = 81). The intention‐to‐treat and per‐protocol analysis could not demonstrate the non‐inferiority of ICR: ten women with ICR could not urinate spontaneously within 6 hours compared with none in the delayed group (risk difference 13.5%, 5.6–24.8, P  = 0.88). However, seven of these women could void spontaneously within 9 hours without additional intervention. Regarding the secondary outcomes, eight women from the delayed group requested earlier catheter removal because of complaints (9.9%). Three women with ICR (4.1%) had a urinary tract infection postoperatively versus eight with DCR (9.9%, risk difference −5.8%, −15.1 to 3.5, P  = 0.215). Women with ICR mobilised significantly earlier (5.7 hours, 0.8–23.3 versus 21.0 hours, 1.4–29.9; P  ≤ 0.001). Conclusion: The non‐inferiority of ICR could not be demonstrated in terms of urinary retention 6 hours after procedure. However, 70% of the women with voiding difficulties could void spontaneously within 9 hours after laparoscopic hysterectomy. It is therefore questionable if all observed urinary retention cases were clinically relevant. As a result, the clinical advantages of ICR may still outweigh the risk of bladder retention and it should therefore be considered after uncomplicated laparoscopic hysterectomy. Tweetable abstract: The advantages of immediate catheter removal after laparoscopic hysterectomy seem to outweigh the risk of bladder retention. Tweetable abstract: The advantages of immediate catheter removal after laparoscopic hysterectomy seem to outweigh the risk of bladder retention.